Ownership structures and sustainability reporting of Malaysian listed companies - Nor Atikah Shafai,; Hafizah Abd-Mutalib,; Saidatul Nurul Hidayah Jannatun Naim Nor-Ahmad, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The study examines the quality of sustainability reporting (SR), the relationship between ownership structures (namely institutional ownership (IO), managerial ownership (MO), and family ownership (FO)) and SR, and the existence of a non-linear relationship between ownership structures and SR based on the inconsistent results of previous studies. The study collected secondary data from the annual and sustainability reports of 261 Malaysian public listed companies (PLCs) in 2018 and 2019 and analysed the data using content analysis. The results report a slight increment in the quality of SR in 2019, and using Ordinary Least Squares (OLS) regression, it is found that only IO has a positive and significant association with SR, which indicates that companies with major institutional shareholdings attain superior SR quality. Further exploration reveals a curvilinear relationship (inverse U-shape) between IO and SR quality, whereby the effect declines when IO reaches a certain threshold. As such, these findings shed light on the changes in investors’ motivation towards their Corporate Social Responsibility (CSR) commitment based on their company holdings, showing the delicate balance needed between oversight and the aligning of interests. This means that large institutional investors in a company should collaborate with management to advocate for policies and practices that support social and environmental objectives that are aligned with the company’s long-term view of value creation.